?DETERMINATION OF PROTEIN, NITRITE AND NITRATE IN ANIMAL PROTEIN SOURCES IN NIGERIA - Adeyeye, E I; Akpambang, V O E; Adebomojoa, I A (Biological Sciences - PJSIR, 2003)
The protein, nitrite and nitrate levels were determined in the body parts of twelve different types of fish, snake, prawn, amphibian and camel, they all serve as animal protein sources. The parts examined for these parameters were: head, gills, internal organs, muscle, bone and skin. All the samples yielded high levels of protein with values ranging between 21.71 g/100 g– 98.80 g /100 g. The nitrite levels ranged between 4.2 mg /kg – 112.06 mg /kg and the nitrate levels ranged between 168.46mg/kg - 4580.67 mg/kg. Nitrate is sparingly used in Nigeria to cure fish and meat. Hence the results of the nitrite and the nitrate might have been due to their levels in the samples. Most of the coefficient of variation values were low in the various sample body parts showing almost homogenous distribution of protein, nitrite and nitrate levels. While the nitrite levels were within the maximum permitted levels, many of the nitrate levels exceeded the maximum permitted levels.